Uterine decidual niche modulates the progressive dedifferentiation of spiral artery vascular smooth muscle cells during human pregnancy - Ma, Yeling; Yu, Xin; Zhang, Lanmei; Liu, Juan; Shao, Xuan; Li, Yu-Xia; Wang, Yan-Ling (Biology of reproduction, 2021)
Uterine spiral artery (SPA) remodeling is a crucial event during pregnancy to provide enough blood supply to maternal–fetal interface and meet the demands of the growing fetus. Along this process, the dynamic change and the fate of spiral artery vascular smooth muscle cells (SPA–VSMCs) have long been debatable. In the present study, we analyzed the cell features of SPA–VSMCs at different stages of vascular remodeling in human early pregnancy, and we demonstrated the progressively morphological change of SPA–VSMCs at un-remodeled (Un-Rem), remodeling, and fully remodeled (Fully-Rem) stages, indicating the extravillous trophoblast (EVT)-independent and EVT-dependent phases of SPA–VSMC dedifferentiation. In vitro experiments in VSMC cell line revealed the efficient roles of decidual stromal cells, decidual natural killer cells (dNK), decidual macrophages, and EVTs in inducing VSMCs dedifferentiation. Importantly, the potential transformation of VSMC toward CD56+ dNKs was displayed by immunofluorescence-DNA in-situ hybridization-proximity ligation and chromatin immunoprecipitation assays for H3K4dime modification in the myosin heavy chain 11 (MYH11) promoter region. The findings clearly illustrate a cascade regulation of the progressive dedifferentiation of SPA–VSMCs by multiple cell types in uterine decidual niche and provide new evidences to reveal the destination of SPA–VSMCs during vascular remodeling. Summary sentence We illustrate a cascade regulation of the dedifferentiation and destination of SPA–VSMCs by uterine decidual niche during vascular remodeling.